Determinasi Kebiasaan Belajar, Motivasi dan Tingkat Kecerdasan terhadap Prestasi Belajar Matematika - Hermawan, Eric (Dinasti Research, 2023)
Abstract: Determination of Study Habits, Motivation and Intelligence Level on Mathematics Learning Achievement is a scientific article of literature study within the scope of Education Management science. This article aims to build a hypothesis of the influence between variables that it will use in further research. In addition to seeing the background influence of an outstanding student in mathematics. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. Sourced from previous research that is relevant to this research. A descriptive qualitative method, library research, from e-books and open access e-journals. The results of this article are: 1) Study Habits are related to Mathematics Learning Achievement; 2) Motivation relates to Mathematics Learning Achievement; 3) Intelligence level relates to Mathematics Learning Achievement. Abstrak: Determinasi Kebiasan Belajar, Motivasi dan Tingkat Kecerdasan terhadap Prestasi Belajar Matematika adalah artikel ilmiah studi pustaka dalam ruang lingkup ilmu Manajemen Pendidikan. Tujuan artikel ini membangun hipotesis pengaruh antar variabel yang akan digunakan pada riset selanjutnya. Selain itu untuk melihat pengaruh yang melatarbelakangi seorang siswa berprestasi di bidang pelajaran matematika. Objek riset pada pustaka online, Google Scholar, Mendeley dan media online akademik lainnya. Bersumber dari penelitian terdahulu yang relevan dengan penelitian ini. Metode kualitatif deskriptif, library research, dari e-book dan open access e-journal. Hasil artikel ini yaitu: 1) Kebiasaan Belajar berhubungan terhadap Prestasi Belajar Matematika; 2) Motivasi berhubungan terhadap Prestasi Belajar Matematika; dan 3) Tingkat Kecerdasan berhubungan terhadap Prestasi Belajar Matematika.